Maternal Perception about Neonatal Jaundice in Eastern Nepal: A Qualitative Study - Dharel, Dinesh; Bhattarai, Asmita (Health Prospect, 2017)
Background: Jaundice is a common problem in newborn babies and mothers have different misconceptions about it in Nepal. This study was conducted to explore mother’s perception about the causes, recognition, management and outcome of neonatal jaundice. Methodology: In-depth interviews were conducted with 32 mothers of infants under six months of age with a history of jaundice in the neonatal period attending the outpatient department of Ilam District Hospital. Audio-taped data were transcribed and analyzed thematically. Results: Most of the mothers recognized jaundice in babies from yellow skin but some noticed it after being alerted by health workers or other people. They perceived jaundice in neonates as a serious condition. However, they were unclear about the cause and attributed it to breach in food restrictions, lack of hygiene or effect of evil spirits. Foods consumed by mothers during and after pregnancy were of concern, not only as a cause but also a remedial measure of jaundice. They usually resorted to traditional measures of avoiding certain foods and reported that health workers did not offer specific remedies and that some health workers even approved such practices. The perceptions of mothers were greatly influenced by family and societal beliefs and practices such as applying oil, sunbathing or avoiding various foods by mothers, often irrespective of advice from health workers. Mother-in-law and the health worker have had the prominent influence in mother’s perception. Conclusion: The perceptions of mothers regarding recognition, seriousness, causes and treatment of jaundice in their newborn babies were mostly guided by their own misconceptions and experiences. However, the family and societal beliefs apparently had a big influence.